A Single-Equation ECM Model of Government’s Investment in Human Capital and Income Inequality in Nigeria - Stephen, Mathew; Idi, Danjuma (Darul Yasin Al Sys, 2024)
This study investigates the impact of government investment in human capital on income inequality in Nigeria using a Single-Equation Error Correction Model (ECM) approach from 1985 to 2023. The analysis involves pre-estimation checks for stationarity and lag order selection, ensuring the methodological robustness of the model. The results indicate stationarity of the variables post-differencing, affirming the reliability of the model. The Parsimonious ECM reveals that increased education expenditure significantly reduces income inequality coefficient of -0.099 (p < 5%), while higher agricultural spending coefficient of 0.078 (p < 5%) leads to a slight rise in inequality. Health expenditure shows no significant impact. The Error Correction Mechanism coefficient of -0.471 (p < 5%) highlights the importance of addressing deviations from long-term equilibrium to reduce income inequality. This study recommends amongst others the significance of targeted policies for education and sustainable agriculture to promote equitable income distribution and economic stability in Nigeria.